2022
DOI: 10.21831/jitp.v9i2.51771
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan media augmented reality sistem tata surya (solar system) pada anak usia 5–7 tahun

Abstract: Penelitian ini bertujuan menghasilkan sebuah produk berupa aplikasi augmented reality atau AR tentang sistem tata surya untuk anak usia 5-7 tahun. Karena pada saat ini sumber belajar untuk mengenal sistem tata surya hanya bisa melalui buku bergambar, alat peraga dan berkunjung ke planetarium namun tidak semua bisa dengan mudah mengakses itu semua dengan menggunakan teknologi akan sangat membantu untuk dapat mengenal sistem tata surya.  Metode yang digunakan dalam penelitian ini ialah metode penelitian RD (Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Literature review research has several procedures that must be followed, as shown in Figure 1. Implementing AR-based Learning Media can be a solution to teaching material about the solar system to support effective learning (Zsalsabilla et al, 2022). This research methodology adopts a literature study to explore research problems (Karimah et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Literature review research has several procedures that must be followed, as shown in Figure 1. Implementing AR-based Learning Media can be a solution to teaching material about the solar system to support effective learning (Zsalsabilla et al, 2022). This research methodology adopts a literature study to explore research problems (Karimah et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…In mastering students' concepts, it can be seen from the results of learning evaluations of students who meet the minimum standards (KKM) (Aris et al, 2020;Emawati & Haka, 2022;Pratama et al, 2020;Rohmah & Anggraito, 2021;Zsalsabilla et al, 2022). The influence on students' science process skills (KPS) by looking at the value of the increase in KPS from 3 classes, namely 1 control class, and 2 experimental classes (Paembonan & Ikhsan, 2021).…”
Section: D Visualization Developer Softwarementioning
confidence: 99%
“…In introducing the solar system to children, children will imagine how to make these planets. Children can sort the size of the order of the planets (Rachmi & Zumi, 2021;Zsalsabilla et al, 2022). The higher the imagination in children, the higher the creativity in children appears.…”
Section: Introductionmentioning
confidence: 99%